Treatment cost of invasive fungal disease (Ifd) in patients with acute myelogenous leukaemia (Aml) or myelodysplastic syndrome (Mds) in German hospitals - Rieger, Christina; Hoppe-Tichy, Torsten; Thalheimer, Markus (Mycoses, 2012)
Invasive fungal disease (IFD) causes increasing morbidity and mortality in haematological cancer patients. Reliable cost data for treating IFD in German hospitals is not available. Objective of the study was to determine the institutional cost of treating the IFD. Data were obtained by retrospective chart review in German hospitals. Patients had either newly diagnosed or relapsed acute myeloid leukaemia (AML) or myelodysplastic syndrome (MDS). Direct medical cost was calculated from hospital provider’s perspective. A total of 108 patients were enrolled at 5 tertiary care hospitals, 36 IFD patients and 72 controls. The vast majority of IFD patients (74%) were diagnosed with invasive aspergillosis. On average, the hospital stay for IFD patients was 12 days longer than in control patients. All patients in the IFD group and 89% of patients in the control group received antifungal drugs. Mean direct costs per patient were €51 517 in the IFD group and €30 454 in the control group. Incremental costs of €21 063 were dominated by cost for antifungal drugs (36%), hospital stay (32%) and blood products (23%). From the perspective of hospitals in Germany the economic burden of IFD in patients with AML or MDS is substantial. Therefore, prevention of IFD is necessary with respect to both clinical and economic reasons.